Understanding History : An Introduction to Analytical Philosophy of History - Jonathan Gorman (Les Presses de l'Université d'Ottawa | University of Ottawa Press, 1992)
Has any question about the historical past ever been finally answered? Of course there is much disagreement among professional historians about what happened in the past and how to explain it. But this incisive study goes one step further and brings into question the very ability of historians to gather and communicate genuine knowledge about the past. Understanding History applies this general question from the philosophy of history to economic history of American slaveholders. Do we understand the American slaveholders? Has the last word on the subject been said? Both the alleged "profitability" of slavery and the purported causes of the American Civil War are philosophically analyzed. Traditional narrative history and econometric history are examined and compared, and their different philosophical assumptions made explicit. The problem of justifying historical methodologies is first set in the wider context of the philosophical problem of knowledge, then lucidly explained and resolved along pragmatic lines. The novelty of Gorman's approach lies in its comparison of narrative with econometric history, its analysis of empathetic understanding in terms of cost-benefit analysis, and its elucidation of the metaphysical presuppositions of empiricism. It stands out especially for the clarity, rigor, and simplicity of its arguments.